Attitudes toward Shock Advertising of Western-European and Serbian University Students With Regard To Public Health Context (Anti-Smoking and Anti-HIV/AIDS Campaigns) - Krstic, Tamara (2007)
The main objective of this dissertation is to examine attitudes toward shock advertising of western-European and Serbian university students with regard to public health context (anti-smoking and anti-HIV/AIDS campaigns). Although the use of shock advertising is widely adopted in practice, there has not been extensive research with regard to this topic. Public health context is of special interest in this dissertation as there is an urge for social marketing on Serbian market. The results of the study showed that attitudes toward shock advertising do not differ largely between two groups of the university students. Furthermore, shock appeal proved to be more effective in non-profit context when compared to other appeals in terms of attention, recall of the advertisements and stated behavioural intentions of the participants. All these show that messages with shocking content have its place in Serbian advertising, however, shock appeals should be used very responsibly, especially in conservative environment such as Serbia.